# How do you evaluate the function when x = -3, 0, and 2 for g(x) = -9x + 1?

Jul 2, 2017

See a solution process below:

#### Explanation:

To evaluate the function you need to replace the value of $x$ for $x$ in the function $g \left(x\right)$.

1) $x = - 3$; substitute $\textcolor{red}{- 3}$ for $\textcolor{red}{x}$ in $g \left(x\right)$:

$g \left(\textcolor{red}{x}\right) = - 9 \textcolor{red}{x} + 1$ becomes:

$g \left(\textcolor{red}{- 3}\right) = \left(- 9 \cdot \textcolor{red}{- 3}\right) + 1$

$g \left(\textcolor{red}{- 3}\right) = 27 + 1$

$g \left(\textcolor{red}{- 3}\right) = 28$

2) $x = 0$; substitute $\textcolor{red}{0}$ for $\textcolor{red}{x}$ in $g \left(x\right)$:

$g \left(\textcolor{red}{x}\right) = - 9 \textcolor{red}{x} + 1$ becomes:

$g \left(\textcolor{red}{0}\right) = \left(- 9 \cdot \textcolor{red}{0}\right) + 1$

$g \left(\textcolor{red}{0}\right) = 0 + 1$

$g \left(\textcolor{red}{0}\right) = 1$

2) $x = 2$; substitute $\textcolor{red}{2}$ for $\textcolor{red}{x}$ in $g \left(x\right)$:

Try this one and see if the previous two examples showed you how to evaluate the function. Good luck!